2022
DOI: 10.12688/f1000research.53539.2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cancer as a comorbid in COVID-19 patients and their characteristics: a meta-analysis study

Abstract: Background: Cancer patients are considered susceptible to coronavirus disease (COVID-19) due to an immunosuppressive state. This study determined the prevalence of cancer as a comorbid in COVID-19 patients, severe events, case fatality rate, history of anticancer therapy associated with severe events, and type of cancer in cancer patients with COVID-19 in the world. Methods: This study used a meta-analysis study approach, sourcing studies from various countries related to cancer and COVID-19. Inclusion and exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…A previously published meta-analysis showed the worldwide prevalence of COVID-19 in adult patients with cancer to be around 4.6%. 8 Other studies have variably reported the prevalence of COVID-19 in patients with cancer to be between 2.6 and 11%. 8 9 Studies done in children hospitalized with COVID-19 in India have reported cancer as a comorbidity in as many as 7-15%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A previously published meta-analysis showed the worldwide prevalence of COVID-19 in adult patients with cancer to be around 4.6%. 8 Other studies have variably reported the prevalence of COVID-19 in patients with cancer to be between 2.6 and 11%. 8 9 Studies done in children hospitalized with COVID-19 in India have reported cancer as a comorbidity in as many as 7-15%.…”
Section: Discussionmentioning
confidence: 97%
“…8 Other studies have variably reported the prevalence of COVID-19 in patients with cancer to be between 2.6 and 11%. 8 9 Studies done in children hospitalized with COVID-19 in India have reported cancer as a comorbidity in as many as 7-15%. 1 10 The reasons for a high proportion of cancer as comorbidity in children with COVID-19 may be manifold.…”
Section: Discussionmentioning
confidence: 97%
“…Based on the calculation of the prevalence of lung cancer in cancer patients with COVID-19, it was found that 20.23% of cancer patients with COVID-19 were lung cancer patients. 62 With an in-depth study of oncogenes and tumor suppressor genes related to lung cancer, it is hoped that it can provide clinical implications, especially related to the prognosis of lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%